1988
DOI: 10.1007/bf01655449
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antiparathyroid antibodies revealing defect expression of a calcium receptor mechanism in hyperparathyroidism

Abstract: Monoclonal antibodies were generated with a hybridoma technique after immunization of mice with intact human parathyroid cells. Three antibodies of the IgG type reacted in immunohistochemistry and immunofluorescense with parathyroid epithelial cells and proximal tubule cells of the kidney but not with a large number of other human tissues. Adenomatous and hyperplastic parathyroid glands of patients with hyperparathyroidism (HPT) demonstrated a reduced immunohistochemical reactivity with the antibodies as compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Interestingly, gp330/ megalin has also been shown to bind Ca2+ in the kidney proximal tubule (23). In addition, monoclonal antibodies that recognize a calcium sensing protein in human parathyroid cells have been shown to recognize a 500-kDa protein and to stain the brush border of the kidney proximal tubule and cytotrophoblast cells of the placenta (36,37), suggesting that the parathyroid calcium sensing protein may correspond to gp330/megalin or a very similar protein. The availability of the gp330/megalin cDNA will greatly facilitate studies designed to clarify the physiological functions ofgp330/megalin and its role in HN.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, gp330/ megalin has also been shown to bind Ca2+ in the kidney proximal tubule (23). In addition, monoclonal antibodies that recognize a calcium sensing protein in human parathyroid cells have been shown to recognize a 500-kDa protein and to stain the brush border of the kidney proximal tubule and cytotrophoblast cells of the placenta (36,37), suggesting that the parathyroid calcium sensing protein may correspond to gp330/megalin or a very similar protein. The availability of the gp330/megalin cDNA will greatly facilitate studies designed to clarify the physiological functions ofgp330/megalin and its role in HN.…”
Section: Discussionmentioning
confidence: 99%
“…[79], Bondeson et al . [65] and others [8082]. On the other hand, capsular invasion can only be seen in a portion of specimens, and vascular invasion in even fewer cases [83,84].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Thus results might reflect what Berger et al [8] demonstrated that the mature granules were pre dominant in the proximity of the cell membrane and the progranules were mainly located in the Golgi area. The reactions to PTH stains by the adenoma cells with relative regularity suggest that the secretion of PTH in the adeno ma cells might have been regulated by the putative cal cium receptor mechanism described by Juhlin et al [9], i.e., the hypercalcemia of hyperparathyroidism may be the result of a decreased sensitivity to extracellular cal cium of the PTH release from pathological parathyroid glands caused by a reduced expression of the putative cal cium receptors of the adenoma parathyroid cells, as well as by the circumference-ionized calcium levels described by Dietel and Holzel [10], It is known that chromogranin A, which is a major soluble protein in the catecholamine storage vesicles of the adrenal medullas and sympathetic nerves [11], is chemically, physiologically and immunologically very similar to SP-I, which is one of the major secretory pro teins in the parathyroid glands [3]. Arps et al [12] and Ravazzola et al [13] used immunocytochemical tech niques at the ultrastructural level to show that PTH and SP-I coexist in the same granules of the parathyroid cells, but in our present study all adenomatous parathyroid glands did not show identical stain positivities for both PTH and chromogranin A or SP-I.…”
Section: Discussionmentioning
confidence: 99%